FILM YASMINE : STRATEGI FILM BRUNEI MENEMBUS PASAR INDONESIA - Ananda, Dhimas Aryo Vipha (Capture : Jurnal Seni Media Rekam, 2017)
Yasmine was an experimental project of Brunei International movie. The movie premiere on 21 August 2014 release to 5 screens (as there are only 5 cinemas) in Brunei and 80 screens in Indonesia, so it was described as the renaissance of Brunei cinemas after 46 years of long sleep. Taking Silat martial arts as background theme for the story. Yasmine movie actually not entirely a trial attempt. There was faith in it, that this movie will be a success because it chose a very typical story. As it was done in Cinderella story that being adopted to Pretty Woman film (1990). Yasmine movie team must be fully aware that the choice of blending romance and martial arts together is always invites many audiences. Deliberately penetrate the Indonesian market was not without strategy, the goals was to brought back film industry as one of creative industry in Brunei along with brings Brunei image go international through Indonesia.Â Keywords: Yasmine Movie, Strategy, Brunei, Indonesia